Efektifitas Problem Based Learning Terhadap Kemampuan Berpikir Kritis Siswa [The Effectiveness of Problem Based Learning on Students' Critical Thinking Skills] - Wuisan, Audrey Caroline; Simamora, Marihot; Siboro, Minerva (Jurnal Teropong Pendidikan, 2024)
The rapid changes in technology today have led to numerous problems and challenges related to global issues that must be addressed wisely. Adapting to this era requires strong thinking skills to quickly acquire new knowledge and make sound decisions. The Problem Based Learning (PBL) model can be used to enhance critical thinking competencies in the teaching and learning process. The objective of this study is to assess the effectiveness of applying the Problem Based Learning (PBL) model in improving students' critical thinking skills in the context of systems of linear equations with two variables. Additionally, this study aims to detect significant differences in critical thinking skills between the experimental and control groups, as well as to investigate whether gender has any impact on critical thinking abilities. The research was conducted at a private XYZ junior high school in Bekasi City from mid-March to April during the second semester of the 2022/2023 academic year. The study used a quasi-experimental research design. The research sample consisted of 28 students in both the control and experimental groups. Purposive sampling was employed, and the instrument used was a set of five essay questions. The results of the mean test analysis indicated that there was no significant difference in critical thinking skills between the experimental and control groups. Furthermore, the correlation test revealed that gender did not have a significant impact on students' critical thinking skills.